AUDITING IN THE AGE OF AI: READINESS AND ROLES OF PROSPECTIVE ACCOUNTANTS, ACCOUNTING EDUCATORS, AND CAMPUS INTERNAL AUDITORS - Christmas William Adi Pratama; David Adechandra Ashedica Pesudo (STIE AMA Salatiga, 2026)
ABSTRACTThe main purpose of this study is to examine the perspectives of prospective accountants, educational accountants, and campus internal auditors on AI usage in the audit process using a qualitative phenomenological approach with interview methods. The findings show varying levels of familiarity with AI across groups. While AI is recognized for its potential to improve audit efficiency and accuracy, concerns remain regarding adaptation challenges and possible job displacement. Key competencies identified for future auditors include data analytics, critical thinking, and technological proficiency. The study highlights the need for accounting education to integrate AI concepts and strengthen these competencies, alongside fostering collaboration between academia and industry. Overall, this research provides insights into the impact of AI on auditing and offers recommendations for both educational and professional adaptation.ABSTRAKTujuan utama penelitian ini adalah untuk mengkaji secara kualitatif pandangan calon akuntan, akuntan pendidikan, dan auditor internal kampus mengenai penggunaan AI dalam proses audit melalui pendekatan fenomenologis dan metode wawancara. Hasil penelitian menunjukkan adanya perbedaan tingkat familiaritas dan pengetahuan AI antar kelompok. Meskipun AI diakui mampu meningkatkan efisiensi dan akurasi audit, terdapat kekhawatiran terkait tantangan adaptasi dan potensi perpindahan pekerjaan. Keterampilan utama yang dibutuhkan meliputi analisis data, berpikir kritis, dan kemahiran teknologi. Oleh karena itu, pendidikan akuntansi perlu mengintegrasikan konsep AI serta mengembangkan keterampilan tersebut, disertai kolaborasi antara dunia pendidikan dan praktik. Penelitian ini memberikan wawasan tentang dampak AI pada audit serta menawarkan rekomendasi untuk adaptasi dalam bidang pendidikan dan profesional..